Physiological profile of adult long-distance trail runners: variations according to competitive level (national or regional) - Oliveira-Rosado, Joana; Duarte, Joao P.; Sousa-e-Silva, Paulo; Costa, Daniela C.; Martinho, Diogo; Sarmento, Hugo; Valente-dos-Santos, Joao; Rama, Luis M.; Tavares, Oscar M.; Conde, Jorge; Castanheira, Joaquim; Soles-Goncalves, Rui; et al. (Inst Israelita Ensino & Pesquisa Albert Einstein, 2020)
Objective: To describe and identify the importance of different indicators of the aerobic and anaerobic fitness of male ultra-trail runners according to their level of participation (regional or national). Methods: Forty-four male ultra-trail runners were assessed (36.5 +/- 7.2 years). They were classified as regional (n=25) and national (n=19). Wingate test was used to assess the anaerobic pathway. A progressive incremental running test was performed and ventilatory thresholds registered, in parallel to heart rate and lactate concentration at the end of the protocol. Comparison between groups was performed using independent samples t-test. Results: No significant differences were found between outputs derived from Wingate test. For aerobic fitness, while examining absolute values, differences were uniquely significant for the second ventilatory threshold (ultra-trail regional runners: 3.78 +/- 0.32L.min(-1); ultra-trail national runners: 4.03 +/- 0.40L. min(-1) p<0.05). Meantime, when aerobic fitness was expressed per unit of body mass, differences were significant for the second ventilatory threshold (ultra-trail regional runners: 50.75 +/- 6.23mL. kg(-1) .min(-1); ultra-trail national runners: 57.88 +/- 4.64mL.kg(-1).min(-1) p<0.05) and also maximum volume of oxygen (ultra-trail regional runners: 57.33 +/- 7.66mL.kg(-1) .min(-1); ultra-trail national runners: 63.39 +/- 4.26mL.kg(-1).min(-1) p<0.05). Conclusion: This study emphasized the importance of expressing physiological variables derived from running protocols per unit of body mass. Also, the second ventilatory threshold appears to be the best and the only aerobic fitness variable to distinguish between trail runners according to competitive level. Maximal oxygen uptake seems of relative interest to distinguish between long distance runners according to competitive level.
Keywords: Physical exertion/physiology; Running; Exercise test; Oxygen consumption; Anaerobic threshold